2001
DOI: 10.1051/rnd:2001128
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of phytate phosphorus by rumen bacteria in a semi-continuous culture system (Rusitec) in lactating goats fed on different forage to concentrate ratios

Abstract: -Experimental data on phytate phosphorus utilisation by ruminants are scarce. The aim of this study was to estimate the phytase activity of rumen micro-organisms when phytate phosphorus supply is high. A semi-continuous culture system fermentor (RUSITEC) was used. The inoculum was obtained from eight goats fed on either high or low forage level diets. Experimental buffers only differed by the nature of phosphorus monosodium phosphate vs. corn sodium phytate. The nylon bags containing 15 g DM of substrate were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
2
14
0
1
Order By: Relevance
“…reported that phytase supplementation did not affect ruminal NH 3 ‐N concentration. The lack of treatment effect on ruminal propionate and butyrate production suggests that supplemental phytase had no effect on gluconeogenesis and lipogenesis . In accordance with a previous study, phytase supplementation did not influence ruminal volatile fatty acids concentrations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…reported that phytase supplementation did not affect ruminal NH 3 ‐N concentration. The lack of treatment effect on ruminal propionate and butyrate production suggests that supplemental phytase had no effect on gluconeogenesis and lipogenesis . In accordance with a previous study, phytase supplementation did not influence ruminal volatile fatty acids concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…The decreased ruminal NH 3 -N levels of phytase supplemented groups at 3 h post feeding could either be the result of a reduction in the proteolytic bacteria population or an increased incorporation of the NH 3 -N into microbial protein as a result of improved microbial growth. 22 It is also possible that supplemental phytase reduced the ruminal degradability of dietary N. However, the effect of phytase supplementation on NH 3 -N became marginal and insignificant with an increasing hours of feeding. Ahmed et al 15 reported that phytase supplementation did not affect ruminal NH 3 -N concentration.…”
Section: Figurementioning
confidence: 99%
“…A study by Clark et al (1986) pointed out that 98% of dietary InsP6 was hydrolysed to inorganic P (Pi) in the gastrointestinal tract of dairy cows. However, in vitro investigations by Godoy and Meschy (2001) showed that in specific situations the ruminal phytase hydrolyses not all P from InsP6. They carried out an experiment with a semi-continuous culture system, infusing Pi or a phytate source into the system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, P availability could be increased by phytase, and then enhance enzyme systems of ruminal microor- ganisms and fermentation of structural carbohydrates (Durand and Komisarczuk, 1988), such as that found on total tract digestion of NDF. In fact, high-grain diets (70%) and low pH induces disturbances in P excretion (Harmon and Britton, 1983) reducing native phytase activity (Godoy and Meschy, 2000). Phytase supplementation improved P digestion and retention, but it was not enough to change P excretion and serum levels as was reported by Knowlton et al (2007).…”
Section: Discussionmentioning
confidence: 92%